Penggunaan Simbol-Simbol Kemiskinan Oleh Para Pengemis Jalanan Di Kota Makassar (Studi Semiotika Fotografi) - Ramli, Abdul Rachmansyah; Cangara, Hafied; Arianto (Fakultas Dakwah dan Komunikasi, 2023)
The existence of beggars in Indonesia can easily be found, starting in crowded centers in big cities, residential areas, residential areas in rural areas. The existence of beggars is considered to damage the beauty of urban planning due to the buildings where they live in prohibited places, are considered to disturb traffic, and are considered to disturb the comfort of others. There are many factors that cause someone to decide to become a beggar. The first is the economic factor. Second, education. Third, is dependency. Fourth, is the environment. Currently, beggars are a serious problem, especially in the provincial capital and big cities including the city of Makassar. their presence often creates problems with urban traffic, order, and security. For this reason, the Makassar city government issued a policy to empower or foster beggars so that they would not become a social burden in urban areas. For this reason, this study examines how the use of symbols of poverty by street beggars in the city of Makassar and portraits of beggars in the study of photographic semiotics.